Using Synchrotron Radiation X-ray Fluorescence (SRXRF) to Assess the Impacts of Shipping Emissions on the Variations of PM10-bound Elemental Species - Siwatt Pongpiachan; Nichada Jearanaikoon; Kanjana Thumanu; Jureerat Pradubsri; Ratchadaporn Supruangnet; Chaisri Tharasawatpipat; Muhammad Zaffar Hashmi; Ronbanchob Apiratikul (Aerosol and Air Quality Research)
Abstract Shipping activities significantly contribute to global atmospheric pollutant emissions. Numerous studies have used synchrotron X-ray fluorescence spectroscopy (SRXRF) to identify elemental species in atmospheric particles, yet few studies have applied this technique for assessing PM10-bound chemical species from shipping emissions. In this study, we conducted simultaneous sampling of PM10 at three air quality observation sites located close to Laem Chabang Sea Port (LCSP) from 24 May to 27 June 2020. The PM10 samples were then chemically characterised using SRXRF at the Beam Line 5.1 Wiggler (BL5.1W) in the Siam Photon Source, Synchrotron Light Research Institute (Nakhon Ratchasima, Thailand). We identified unique features in the SRXRF spectra of PM10 samples collected from the site adjacent to LCSP. The average percentage contributions of selected metals at LCSP occurred in the order of Fe > Cu > Te > As > Br > Kr > Mn > Cr > Ni > V > Ti > P > Se > S > Cl, which is in good agreement with the results of previous studies conducted in Bangkok. Although some previous studies highlight the importance of V/Fe as the diagnostic binary ratio that can be used as a chemical proxy for categorizing shipping related particles, this application can be problematic-particularly in the atmospheric environment with high contents of iron-rich dust aerosols. In stead of employing V/Fe, the diagnostic binary ratios of As/V and Se/V can be considered as alternative geochemical tracers for classifying shipping emissions associated aerosols. By applying the concept of enrichment factor (EF), Se is exceedingly enriched in all observatory sites indicating that industrial emissions were the dominant contributor of Se at the ambient air of Lam Chabang. Hierarchical cluster analysis (HCA) successfully classify a group of V, Ti, Ga, and Ni at all sampling sites, which may be caused by shipping activities coupled with industrial emissions.